Policing across divides: a comparative study of police practices in Nyanga and Sea Point - Schick, Cornelius Georg (Department of Public Law, 2025)
This master's thesis presents a comparative analysis of police practices in two socio-economic areas of Cape Town, South Africa: Nyanga and Sea Point. The study explores how socio-economic status and crime burden influence policing strategies and how these factors contribute to reinforcing or alleviating social inequalities. The research utilises a qualitative approach, in-depth interviews with police officers provide a nuanced understanding of the dynamics at play. The study finds that policing practices in Nyanga, an area characterised by low socio-economic status and high crime rates, are predominantly reactive, with a strong focus on crime suppression. While addressing immediate safety concerns, this approach inadvertently perpetuates a cycle of mistrust and alienation between the police and the community. In contrast, in Sea Point, an area with higher socio-economic status and lower crime rates, policing is more proactive and community-oriented. This strategy fosters a positive relationship between the police and the residents, enhancing trust and cooperation. The thesis demonstrates that socio-economic factors and crime burden indirectly influence policing practices by affecting crime patterns and community-police relations. The findings emphasise the necessity of a more comprehensive approach to policing that takes into account underlying socio-economic factors and prioritises community engagement, particularly in areas with higher crime rates and lower socio-economic status. This research contributes to the ongoing discourse on policing and social inequality. It provides insights into how different approaches can either mitigate or exacerbate the underlying socio-economic disparities within urban communities.